2019
DOI: 10.1007/s40201-019-00337-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the selected heavy metal and metalloid contents in various types of plastic bags

Abstract: The immense plastic bags (PBs) consumption is the potential threat for environment and public health due to discharging toxic pollutants (i.e., metals and metalloids) throughout its entire life cycle. The purpose of the study was to investigate the heavy metal (HM) contents in PE, HDPE, LDPE and PVC bags with several colors and applications. The HM contents in the PB were analyzed by ICP-OES after acid digestion. Results demonstrated that the HM contents in PB notably disagreed based on the used polymer types,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 45 publications
(59 reference statements)
1
17
0
Order By: Relevance
“…Except of gloves, trace elements were detected in raw PE ( Munier and Bendell, 2018 ), particles of plastic bags ( Alam et al, 2019 , Alam et al, 2018 ), litters ( Nakashima et al, 2011 , Turner, 2017 ), micro- and macro plastics ( Munier and Bendell, 2018 , Turner et al, 2019 ), and debris ( Prunier et al, 2019 ) made of PE (both LDPE and HDPE). Ba, Cd, Cr, Cu, Pb and Zn concentrations were studied most often and the obtained results are collected in Table 2 .…”
Section: Dpgs Influence On the Environmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Except of gloves, trace elements were detected in raw PE ( Munier and Bendell, 2018 ), particles of plastic bags ( Alam et al, 2019 , Alam et al, 2018 ), litters ( Nakashima et al, 2011 , Turner, 2017 ), micro- and macro plastics ( Munier and Bendell, 2018 , Turner et al, 2019 ), and debris ( Prunier et al, 2019 ) made of PE (both LDPE and HDPE). Ba, Cd, Cr, Cu, Pb and Zn concentrations were studied most often and the obtained results are collected in Table 2 .…”
Section: Dpgs Influence On the Environmentmentioning
confidence: 99%
“…in the range from 92.5 to 29200 µg/g in beached filamentous plastic litters ( Turner, 2017 ). Mn was determined in PE, HDPE and LDPE bags, but their content varied from below detection limit to 25.1 µg/g ( Alam et al, 2019 , Alam et al, 2018 ). Other heavy metals (Bi, Hg, Ni, Sn, Sr, Ti, and V) rarely occurred in PE particles or their concentration was relatively low ( Prunier et al, 2019 , Turner, 2017 , Turner et al, 2019 ).…”
Section: Dpgs Influence On the Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, across the globe few empirical studies have reported levels of heavy metals in an array of plastics types. Most of the researches are dealing with levels of heavy metals in electronics and single use plastics in contacts with food or plastics in waste [20] [23]. For instance, A study on plastic toys imported from China to Northwestern Nigeria determined lead, cadmium, nickel, copper, zinc, chromium, cobalt and manganese with 17% of them having high levels more than USFDA recommendations; which poses threat to children exposed to these toys, and public health [19].…”
Section: Introductionmentioning
confidence: 99%